Bulking Agent in Dry Anaerobic Digestion as a Key Factor for the Enhancement of Biogas Production - Poblete-Castro, I (Elsevier B.V., 2024)
Dry anaerobic digestion (dry-AD) is an attractive process for solid wastes such as agri-food waste. However, some limitations mainly associated to lack of effective mixing, can hinder the methane production capacity of the systems. Bulking agent (BA) has been proposed as a solution to the compaction issues in systems without mechanical agitation, such as leaching bed reactors. However, effects of BA are still not clear, and, thus, the factors to consider for its dose has not been optimized yet. This work studies the effect of BA in dry-AD. Two substrates with different characteristics were proposed as models, bean peel as a lignocellulosic substrate and a mixture of food waste as a readily biodegradable substrate. Inert plastic rings were used as BA at different BA:S ratios. Assessed BA:S ratio did not affect the performance of methane production for the lignocellulosic waste, but it did significantly affect to the easily biodegradable substrate, showing up to a 28% of methane production increase. This result could be due to the presence of lignocellulosic compounds in the bean peel, behaving like a natural BA. In assays with an increased bed height, the compaction of the system was more severe, resulting in the rapid acidification of the processes. At these conditions, the positive effect of BA addition was more marked, allowing methane production and no acidification of the system. Thus, the addition of BA is a suitable strategy for improving methane production or stability in dry-AD systems without requiring the stirring of the systems. © 2024 The Authors